An energy mix policy to address the wicked problem of energy insecurity in South Africa - Khumalo, Nduduzo S. P. (University of the Witwatersrand, Johannesburg, 2023)
Eskom is struggling to consistently supply electricity as required by the country, therefore failing to keep the lights on. Eskom has been producing less and less power over the years, a wicked problem for an economy faced with poverty, unemployment and inequality. This wicked problem in the energy (electricity) supply system has impacted a large number of stakeholders. These include, mining, commercial and industrial, agriculture, households and the entire Southern African Power Pool and its customers. As a result, this energy insecurity problem of all the stakeholders is therefore considered as a wicked problem that does not have a straightforward solution. This research investigates the impact and challenges in the economy and society at large as a result of wicked problem, energy insecurity, and assesses what can be done by the society to mitigate these challenges and then propose a solution to the identified problem in the form of Energy Mix Policy. It does so by using secondary data from multiple database sources. This research argues that the energy insecurity (unreliable energy supply) in South Africa is a wicked problem. It affects multiple stakeholders from the business communities, government, industries, and everyone in the society, even touching climate change environmental management sectors. This also affects all economic industries, commercial businesses, water supply, hospitals, telecommunications, and transportation sectors, etc. as they all require power to operate, and therefore a solution would require all these stakeholders to be involved and act collectively together in finding a solution that can assure energy security for all
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Energy Security; Wicked Problems; Energy Insecurity; Energy Mix Policy; Economic Development; Unemployment; Society; South Africa; Poverty; UCTD; SDG-7: Affordable and clean energy